Islamic Financial Literacy in The Digital Era: A Phenomenological Exploration of Generation Z in Indonesia - Annisatul Ainiyah (SHACRAL: Shari'ah Economics Review Journal, 2024)
The rapid expansion of Islamic finance in Indonesia has heightened the importance of Islamic financial literacy, particularly among Generation Z as the country’s largest demographic cohort and future economic actors. Despite growing access to Islamic financial products and digital financial services, evidence suggests that Islamic financial literacy levels remain relatively low, raising concerns about the sustainability and inclusiveness of Islamic financial development. This study aims to explore Islamic financial literacy among Generation Z in Indonesia through a qualitative descriptive phenomenological approach based exclusively on secondary data. Drawing on academic literature, official statistical reports, regulatory documents, and institutional publications, this study seeks to understand how Islamic financial literacy is conceptualized, constructed, and experienced within contemporary socio-economic and digital contexts. Rather than measuring literacy quantitatively, the research focuses on identifying shared meanings, interpretive patterns, and structural conditions that shape Generation Z’s engagement with Islamic financial knowledge and practices. The phenomenological analysis highlights how Islamic financial literacy is commonly understood as a combination of financial knowledge, religious awareness, and ethical orientation, yet often manifests in fragmented and instrumental forms. The findings reveal that digitalization plays a pivotal role in mediating Islamic financial literacy among Generation Z. Social media, fintech platforms, and digital influencers function as primary sources of information, offering both opportunities for wider outreach and risks of superficial understanding. Furthermore, institutional trust in regulatory bodies and Sharia authorities emerges as a key mechanism through which Generation Z navigates complex Islamic financial products, sometimes substituting critical understanding with reliance on certification and branding. This study contributes to the Islamic economics and finance literature by extending discussions of Islamic financial literacy beyond quantitative indices toward an interpretive, context-sensitive understanding. Practically, the findings underscore the need for integrated literacy strategies that combine ethical reflection, digital engagement, and inclusive education. Strengthening Islamic financial literacy among Generation Z is essential not only for individual financial well-being but also for advancing the broader objectives of Islamic economics, including social justice, financial inclusion, and sustainable development.